TENDING TO TWO HEARTS: INVESTIGATING THE EMOTIONAL JOURNEY OF SELF-CARE AND INFANT CARE IN KOREAN WOMEN PRONE TO POSTPARTUM DEPRESSION - Emily , Anne Johnson; Kim, Min-Ji; Smith, Jonathan David (Research Journal of Health, Medicine and Nursing, 2024)
In South Korea, traditional postpartum care and support are provided by the mother or mother-in-law for at least three weeks following childbirth, aiding the new mother in her physical and psychological recovery and infant care (Song, Chang, & Kim, 2008). This early postpartum period serves as a crucial transition time during which mothers acquire the skills and understanding needed to fulfill their roles and responsibilities as parents (Epifanio, Genna, DeLuca, Rocella, & La Grutta, 2015). Knowledge about newborn care, infant development, and parental roles and responsibilities is gained during this period. Therefore, healthcare professionals play a vital role in assisting women in the postpartum phase (Razurel, Kaiser, Antonietti, Epiney, & Sellenet, 2017).